Increasing Students’ Reading Comprehension and Learning Interest by Using Snowball Throwing Method at The Tenth-Grade Students of Assalam IBS - Wianto, Tukir; Firdaus, Masagus; Mulyadi (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2025)
This study investigates the effectiveness of the Snowball Throwing Method in improving students' reading comprehension and learning interest among tenth-grade students of Assalam IBS. Conducted as classroom action research, the study involved 30 students from class X.C over two cycles. Data were collected through reading comprehension tests, learning interest questionnaires, observations, and interviews. The data were analyzed using descriptive statistical analysis for quantitative data, which includes the results of the reading comprehension test and the learning interest questionnaire. Meanwhile, qualitative data, which consists of observation and interview results, were analyzed using descriptive narrative data analysis techniques. The findings reveal significant improvements across both cycles. In Cycle 1, the average reading comprehension score was 67.67, with an average learning interest score of 98.80. By Cycle 2, these scores increased to 77.75 for reading comprehension and 112.30 for learning interest. The result was also supported by data of observation and interview to the students related to learning activity by using snowball throwing method. The results indicate that the Snowball Throwing Method effectively enhances both reading comprehension and student engagement. This method encourages active participation and collaborative learning, fostering a more interactive and stimulating classroom environment. The study concludes that the Snowball Throwing Method is a practical approach to address challenges in reading comprehension and learning interest among high school students.